Evaluation of pharmacist interventions and commonly used medications in the geriatric ward of a teaching hospital in Turkey: a retrospective study - Ertuna, Elif (Clin Interv Aging, 2019)
PURPOSE: Aging increases the prevalence of diseases. The elderly population is consequently often exposed to complex medication regimens. Increased drug use is one of the main reasons for drug-related problems (DRPs). The primary objective of this study was to define and classify DRPs, pharmacist interventions, and frequently prescribed medications in relation to possible DRPs in patients admitted to the geriatric ward of a teaching hospital in Turkey. PATIENTS AND METHODS: Pharmacist medication review reports for 200 orders of 91 patients (mean age: 80.33±0.46) were analyzed retrospectively. RESULTS: A total of 1,632 medications were assessed and 329 interventions were proposed for possible DRPs in 156 orders. A total of 87.5% of the patients used five or more drugs (mean: 8.17±0.23). The number of DRPs per order was higher when polypharmacy was present (1.04±0.15 vs 1.66±0.11, P<0.05). In 71.31% of the cases, adverse drug events were recognized as the problem. The principal cause of possible DRPs was determined as drug interactions (40.12%). Only 22 potentially inappropriate medications were prescribed. The most common interventions included monitoring drug therapy (31.0%), stopping the drug (20.06%), and changing dosage (13.98%). The acceptance rate of pharmacist interventions by treating geriatrician was 85.41%. The most frequently prescribed drugs were for the nervous system, alimentary tract and metabolism, and cardiovascular system (n=358, 314, and 304, respectively). The pharmaceutical forms of 23 drugs were deemed inappropriate by pharmacists. CONCLUSION: Clinical pharmacy services are still not properly implemented in Turkey. The study highlights ways in which clinical pharmacy services can be instrumental in a geriatric ward. The high acceptance rates of pharmacist recommendations concerning a wide variety of DRPs and different classes of drugs indicate that advanced collaboration among geriatricians and pharmacists is possible in interdisciplinary geriatric assessment teams in Turkey.